Nutritional Survival Strategies. Polish political refugees in England against the prospect of malnutrition and famine in the 1830s and 1840s - Marchlewicz, Krzysztof (Perspektywa stołu, 2023)
In the 19th century, one of the consequences of the emigration was often breaking direct contact with the culinary culture of the home country. This break-up gave rise to longing and discomfort, which the emigrants tried to alleviate by recreating the flavors of their homeland in exile. However, for many poorer refugees the fundamental threat was disturbance of the very foundations of their material existence and the need to deal with the perpective of malnutrition and hunger. This text analyzes the strategies used by Polish refugees in England after the November Uprising to avert the risk of starvation. Various methods were discussed successively, which allowed the less wealthy ex-insurgents to compile a daily menu – which was not easy task in 19th century Britain, characterized by high cost of living. Among these methods were indicated both those that were the initiatives of the emigrants themselves and those that resulted from the imitation of poorer Britons by Poles.